Geatão pública: uma investigação empírica sobre as improbidades administrativas nos municípios cearenses - Dantas, Márcia de Azevedo Franco (2009)
Investigating the determinants for the occurrence of administrative improbity acts, as well as the persistency of such acts in the municipalities of the State of Ceará, is the main focus of this investigation. Besides the scarcity of studies in the literature, the relevance of this investigation is supported by the high improbity proportion testified in the municipalities among the diverse sectors of the public administration which account for over 40%, according to official data from State Bureau for Municipality Accounting (TCM-CE) in the period 2002-2004. Based upon discrete choice models, a profile of the municipalities was done from testing several variables identified by economic size, fiscal account size and public debt, which might conduct to irregular acts by the public administrators. The results led to the conclusion that there is indeed evidence for persistency of dishonesty acts in the municipalities’ accountings in the period of analysis. Yet, it was not possible to identify common pattern of improbity acts among the municipalities for the entire period, although they do occur randomly, regardless of specific features. Also, the research sought to highlight the important role of public administration in fighting against corruption, in practicing a bureaucracy balanced between legality and efficiency, and providing solid political institutions.